The Role of Procalcitonin to Determine Infection in Diabetic Foot Ulcer: An Evidence-Based Case Report - Ardian, Laurentius Johan (Journal of Diverse Medical Research: Medicosphere, 2024)
Introduction: Early diagnosis infection in diabetic foot patients remains challenging. Several biomarkers have been used as a diagnostic tool, including procalcitonin. However, the performance of this examination is still questioning. Aim: This evidence-based case report aims to assess the performance of procalcitonin level to distinguish between infected and non-infected diabetic foot. Method: Literature searching was performed in Medline, Cochrane, EBSCO, Scopus, and also hand searching. Only articles with cuts off outcome were included. Result: Patients with diabetic ulcer infection has a higher procalcitonin level compare with those who did not have a disease. Several cuts off provide to diagnose infection in the diabetic ulcer. Uzun et al. found 0.08 and 0.1 as a cut off which performed good specificity and sensitivity. Conclusion: Procalcitonin helps us to distinguish non-infected and infected diabetic ulcers. The best cut-off value was 0.5 with the 54 % sensitivity and 100 % specificity.